Pengaruh Kualitas Produk dan Citra Merek terhadap Minat Beli Laptop Acer pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Pembangunan Nasional “Veteran” Jawa Timur - Hermawan Kristanto; Hery Pudjoprastyono (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2021)
In the development of the era of laptops, many are presented with different specifications and advantages. Manufacturers compete with each other to win the hearts of consumers by presenting their respective superior products. Thus the Acer company needs to improve the quality of its products and brand image in order to be able to attract consumer buying interest. This study aims to determine the effect of product quality, brand image on buying interest in Acer laptops. The population in this study were students of the Faculty of Economics and Business, UPN